MENYIKAT GIGI DENGAN METODE DEMONSTRASI DAN BERMAIN PERAN TERHADAP INDEKS DEBRIS PADA SISWA-SISWI SD NEGERI 173546 BALIGE - Intan Aritonang (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2021)
Brushing teeth is a commonly recommended way to clean the surface of the teeth and mouth from equalization and debris which are the main causes of dental and oral diseases. Tooth brushing techniques can be provided with a variety of methods, including demonstration methods and role playing.. This type of research was descriptive study with a survey method that aims to find out the description of brushing teeth with demonstration and role playmethod on the index debris. The sample in this study were all fifth grade students of SD Negeri 173546 Balige, totaling 30 people. The results showed that before brushing teeth with a demonstration method showed that the average index debris was 1.9 and the average index debris after being 1. While brushing teeth with the role playing method, the average debris index before was 1.9 and the average average after becoming 0.6. Difference in decrease of index debris after being given a demonstration method and playing a role of 0.4. The conclusion of this study is brushing with demonstration methods and playing a role both experience decreased index debris. The results of this study are that the role playing method is more effective than the demonstration method. It is expected that the school should be able to use this method in maintaining oral health, especially brushing teeth